Security System Using Lora Transmission : Applications in Warehouse - Charisma Dimas Affandi; Pauladie Susanto; Musayyanah; Yosefine Triwidyastuti (JEECS (Journal of Electrical Engineering and Computer Sciences), 2021)
The widespread theft of storage warehouses, especially in rural areas, rarely supported by communication technology. A system was created to improve the security of storage warehouses with LoRa transmissions capable of sending data remotely. When there is an open warehouse door, this system will send the data to the warehouse owner's house with LoRa transmission in the form of open door information to detect theft early. The LoRa transmission test results in the early morning hours resulted in a success rate of 99.61% at a distance of 1.40 Km and a success percentage of 99.06% at a distance of 2.15 Km. The entire system has been tested at a distance of 1.4 Km, and the early morning hours resulted in a percentage success of 95.15%. An error occurred due to packet loss. As evidenced by the further distance of the test, the percentage of success will be reduced. Besides that, cellular connections around the testing area also affect. Where in the afternoon, cellular network traffic is denser compared to the early morning hours. As evidenced by the results of testing in the afternoon, there was a decrease in the percentage success by 5%. Overall, the security system created and tested resulted in the conclusion that the security system in this study had shown promising results.